2013
DOI: 10.1111/acem.12254
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Acute Mesenteric Ischemia: A Systematic Review and Meta-analysis

Abstract: Objectives Acute mesenteric ischemia is an infrequent cause of abdominal pain in emergency department (ED) patients; however, mortality for this condition is high. Rapid diagnosis and surgery are key to survival, but presenting signs are often vague or variable, and there is no pathognomonic laboratory screening test. A systematic review and meta‐analysis of the available literature was performed to determine diagnostic test characteristics of patient symptoms, objective signs, laboratory studies, and diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
137
3
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(159 citation statements)
references
References 83 publications
(181 reference statements)
7
137
3
12
Order By: Relevance
“…The first, being that in spite of a thorough history and an abundance of clinical data, the critical piece of data for making the diagnosis of mesenteric ischemia is a contrasted CT scan. A meta-analysis examining the diagnosis of acute mesenteric ischemia found that among all of the data collected when working towards a diagnosis of acute mesenteric ischemia, the CT angiogram was the most important and definitive [3]. Accordingly, it would seem that no argument would be raised regarding the use of contrasted imaging in the evaluation of acute mesenteric ischemia.…”
Section: Discussion and Teachable Momentmentioning
confidence: 99%
“…The first, being that in spite of a thorough history and an abundance of clinical data, the critical piece of data for making the diagnosis of mesenteric ischemia is a contrasted CT scan. A meta-analysis examining the diagnosis of acute mesenteric ischemia found that among all of the data collected when working towards a diagnosis of acute mesenteric ischemia, the CT angiogram was the most important and definitive [3]. Accordingly, it would seem that no argument would be raised regarding the use of contrasted imaging in the evaluation of acute mesenteric ischemia.…”
Section: Discussion and Teachable Momentmentioning
confidence: 99%
“…[9] Biphasic contrast CT scanning is the gold standard in the diagnosis of AMI. [10,11] Due to non-specific symptoms and clinical manifestations, accurate diagnosis may be delayed, and this delay may increase the mortality and morbidity rates. In our study, we diagnosed the AMI patients by dynamic CT angiography and we recommended it for all patients suspected for AMI.…”
Section: Discussionmentioning
confidence: 99%
“…2 The overall operative mortality rate is roughly 50% 2 and varies depending on such factors as the extent of gangrene, length of resection and reversibility of the ischemia.…”
Section: Mortality Rates Are High Even With Appropriate Managementmentioning
confidence: 99%
“…1 In stable patients in whom clinical suspicion is high, computed tomography angiography is usually the most appropriate diagnostic test, with a sensitivity and specificity close to 95%. 2 However, in patients with peritoneal findings, the diagnosis is usually made with diagnostic laparoscopy 3 or laparotomy. 4 CMAJ invites submissions to "Five things to know about …" Submit manuscripts online at http://mc.manuscriptcentral .…”
mentioning
confidence: 99%
See 1 more Smart Citation